General guideline for business plan writing (part 1) - Nik Jaafar, Nik Fazlin Hiryati; Nik Hassan, Nik Fakrulhazri; Ibrahim, Norlaila; Mat Zin, Sakinah; Md Noor, Jannah Munirah (Fakulti Pengurusan Perniagaan, UiTM Terengganu, 2021)
It is agreed that the content of the business plan will be the main selling point in order to convince readers, but the overall structure and look of the business plan are equally important. The readers will be distracted by unpleasant look and presentation of the pages shown. Discussed below are among the matters that must be taken care of in order to produce a good business plan.